Foundations of primary psychological assistance during crises - Chinar, Samia; Boulahbal, Aya (Journal of Human Sciences, 2021)
Disasters, health crises and wars are one of the most traumatic events experienced by the individual since ancient times, which have contributed greatly to the emergence of psychological first aid programs, the latter is an approach to provide basic psychological support to individuals suffering from the impact of traumatic events, it is caring Basic pragmatism based on the focus on listening, not forcing talk, assessing and meeting basic needs, as well as encouraging them, with a view to reducing the initial distress caused by traumatic events or large-scale crises and enhancing performance and adjustment in the short term And the remote. Through this scientific article, we showing the foundations of primary psychological assistance, which psychologists must be aware of in order to be able to provide in the event of a traumatic event.